Roles of stakeholders in the provision of Inclusive education for secondary school students with hearing impairment in Nigeria (2019)
This paper examined the roles of stakeholders in the Provision of inclusive education for secondary school students with hearing impairment in Nigeria. The meaning and benefits of inclusive education were extensively discussed. The education stakeholders were identified as the parents, teachers, policymakers, and society, and their roles were discussed. The importance of depoliticizing inclusive education for national development, and the need for Public-Private Partnership in the provision of inclusive education for secondary school students with hearing impairment in Nigeria were discussed. Recommendations were made based on the Submission made by the author.